A210 THE IMPACT OF IBD REFERRAL QUALITY ON WAIT TIMES. (1st March 2018) - Mathias, H; Heisler, C; Morrison, J B; Jones, J
Abstract: Background: Due to health and socioeconomic burdens associated with Inflammatory Bowel Disease (IBD), timely access to specialist care is important. In Canada, speciality gastroenterology (GI) care is accessed only by referral. To receive timely care, referrals must include a high quantity/quality of information. In 2012, 2 in 3 Canadian specialist physicians surveyed reported a lack of basic information on referrals. Referrals are often returned to referring physicians for more information, which is costly to patients and physicians. Some studies have examined referral quality, but not how the quality of referrals influences patient outcomes. Aims: The objectives of this study are to determine if referrals to the Nova Scotia Collaborative IBD (NSCIBD) program contain enough information to allow accurate triage for timely access to care, and how the quality of initial referrals to the NSCIBD program inform patient outcomes (e.g. disease flare, hospitalization) while waiting for specialist consultation. Methods: This is an ongoing retrospective cohort study of patients referred for appointments in the NSCIBD program between August 2016–2017. A sample size of 200 was required to have a power of 0.80 (p=0.50). Patients were included if they were referred for a first visit to the NSCIBD program for confirmed or suspected IBD. Referrals were excluded if they were for a non-IBD-related concern, an endoscopic test, or a follow up. Referrals were evaluated using a data abstraction form developed with an IBD specialist and two GI nurse practitioners. Based on the information included, referrals were classified as either low, moderate, or high quality. Descriptive statistics were used for a preliminary analysis of the baseline, cross-sectional data. Results: To date, 150 records have been reviewed. There were 9 high quality referrals (6.0%), 32 moderate (21.0%), and 109 low quality referrals (72.7%). The majority of referrals were from family doctors (49.3%) with 81.1% of those being low quality. On average, patients with low quality referrals had a mean wait time of 48.0 days (SD=173.3, range=0–873 days) until triage and a mean wait time of 29.9 weeks (SD=37.3, range=0–160 weeks) to be seen by a GI. Patients with moderate-high quality referrals had a mean wait time of 16.6 days (SD=21.9, range=0–81 days) for triage and a mean of 16.7 weeks (SD=14.9, range=1–65 weeks) to be seen by a GI. Conclusions: The majority of referrals analyzed to date are low quality and have longer average wait times. Prolonged wait time is concerning given its documented impact on patient satisfaction, quality of life and administrative resources. Further analysis will focus on whether there are significant differences in patient outcomes between the qualities of referrals, and factors informing referral quality. Moving forward, higher levels of referrer education, as well as patient awareness and advocacy are needed. Funding Agencies: CIHRNova Scotia Health Authority Fund